PID Sensor Controlled Automatic Wheelchair for Physically Disabled People - et. al., Dr. V. Balambica, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Automation in medical mechatronics for physically disabled people has been researched in many institutes and various medical fields, and many scientists and researchers have developed a various prototype which is controlled by a gesture, RC, accelerometer, automatic control with the joystick in the functioning of a wheelchair for physically disabled people, but the control of the equipment using only PID (Passive Infrared Detector) sensor has yet to be developed. In this paper, we have mainly focused on the cost effective factor of developing a cheap automatic wheelchair for low-income families. This wheelchair works on the simple principle of a PID SENSOR as the Title suggests that the wheelchair is controlled using a PID SENSOR using hand obstruction so that the reflected infrared light falling on the PID sensor will give the received information to the Arduino board to give a signal to the motor to move the wheelchair as per the person’s desire to the desired direction. We have mounted PID sensors for left, right, and reverse direction also. So, when the Infrared sensor module receives a reflected infrared ray to the IR RECIEVER then the reflected ray is initiated to give the signal from the obstruction of the OBJECT(in our case – HAND/FINGER) and thus the wheelchair starts to move. And for stopping the wheelchair simply take the obstruction made by the OBJECT (HAND) above the PID sensor then no infrared ray will be received by the IR RECIEVER then it will stop giving a signal to the motors to move any further and thus bring the wheelchair to a stationary position. So, this wheelchair design allows self-control using Infrared Sensors and a microcontroller (Arduino Uno) based circuitry. This design is to bring support for the physically disabled people with very low income who cannot afford to buy a fully functional automatic wheelchair at a high cost. The entire setup is done through a normal wheelchair with DC motors and a control unit consisting of IR sensors, Arduino Uno, beeper, motor driver modules, a switch, and a battery.